السجالات الصحفية بين قيادات الإصلاحيين والاِندماجيين 1900م- 1950م - خيرة كعبوش; د/ أمحمد يزير (جامعة عمار ثليجي الاغواط, 2023)
ملخص: من خلال دراستنا للموضوع تبين أن الصحف تعتبر من أهم الوسائل التي تهدف إلى صحوا الأفكار وبعث روح المقاومة الفكرية التي جسدها الشعب الجزائري من خلال الصحف التي مثلها الاِتجاهين . الاتجاه الاصلاحي : تزعمه عبد الحميد بن باديس وأسس جمعية العلماء المسلمين وطالب بالحفاظ على الشخصية الوطنية والدين الإسلامي ومحاربة البدع ونشر التعليم بين الشبان. الاِتجاه الاِندماجي : تزعمه فرحات عباس وأسس حزب فيدرالية المنتخبين المسلمين الجزائريين وطالب بالمساواة والاندماج مع الحفاظ على الشخصية العربية الإسلامية. - لذلك كان للصحف دورا كبيرا في إبراز السجال الفكري القائم بينهما. الكلمات المفتاحية : المقاومة الفكرية –الاتجاه الاصلاحي –جمعية العلماء المسلمين –الاتجاه الاندماجي حزب فدرالية المنتخبين المسلمين . Summary : Through our study of the subject, it become clear that newspapers are one of the most important id means aimed at erasing ideas and instilling the spirit of intellectual resistance embodied by the Algerian people through newspapers. Representing two directions: The first direction is led by Abdel Hamid Ben Badis, who fonded thé Anociation of Muslim scholars, and called for preserving national identity and Islamic neligion, combating innration, and spreading education among yong people. - The second direction: Is led by Farhat Abbas who founded the Algerian Muslim elected officials Federation party calling for equality and integration while preserving Arab- Islamic identity Vous avez envoy Therefore, newspapers played a significant role in highlighting the intellectual debate between them. -Keywords: Intellectual resistance- reformist direction- Association of Muslim Scholars- integrationist direction- Algerian Muslim elected officials Federation party